1998
DOI: 10.1126/science.281.5383.1677
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the ATM Kinase by Ionizing Radiation and Phosphorylation of p53

Abstract: The p53 tumor suppressor protein is activated and phosphorylated on serine-15 in response to various DNA damaging agents. The gene product mutated in ataxia telangiectasia, ATM, acts upstream of p53 in a signal transduction pathway initiated by ionizing radiation. Immunoprecipitated ATM had intrinsic protein kinase activity and phosphorylated p53 on serine-15 in a manganese-dependent manner. Ionizing radiation, but not ultraviolet radiation, rapidly enhanced this p53-directed kinase activity of endogenous ATM.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

45
1,416
2
8

Year Published

1999
1999
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,830 publications
(1,479 citation statements)
references
References 18 publications
45
1,416
2
8
Order By: Relevance
“…The Cterminal half of the ATM gene contains sequence similarity to several DNA checkpoint genes and a domain homologous to phosphatidylinositol 3-kinase, consistent with the notion that the ATM protein functions as a protein kinase that phosphorylates p53 on Ser15 and thereby contributes to p53 activation (Banin et al, 1998;Canman et al, 1998). It is noteworthy that the phenotypic defects in AT are not merely the result of insu cient p53 induction after IR.…”
Section: Role Of P53 In Growth Arrestsupporting
confidence: 71%
See 1 more Smart Citation
“…The Cterminal half of the ATM gene contains sequence similarity to several DNA checkpoint genes and a domain homologous to phosphatidylinositol 3-kinase, consistent with the notion that the ATM protein functions as a protein kinase that phosphorylates p53 on Ser15 and thereby contributes to p53 activation (Banin et al, 1998;Canman et al, 1998). It is noteworthy that the phenotypic defects in AT are not merely the result of insu cient p53 induction after IR.…”
Section: Role Of P53 In Growth Arrestsupporting
confidence: 71%
“…Several protein kinases can phosphorylate distinct domains of p53 in Structure and function of p53 protein P May and E May vitro. For example the DNA-PK (DNA-activated protein kinase), ATM kinase, (Banin et al, 1998;Canman et al, 1998) and CK1 (casein kinase I-like protein kinase), CDK-activating kinase (CAK) each phosphorylate di erent sites in the N-terminal transactivation domain of p53 (reviewed by Steegenga et al, 1996;Giaccia and Kastan, 1998;Chernov et al, 1998) (Figure 1). These phosphorylation events e ect the transactivation function of p53.…”
Section: Regulation Of P53 Functionmentioning
confidence: 99%
“…It is well established that ATM kinase activity is enhanced by DSBs (Banin et al, 1998;Canman et al, 1998), however, ATM was also shown to be phosphorylated in the absence of visible DSBs, for example, following replication arrest by thymidine (Bolderson et al, 2004). Previous studies have shown that following DSBs phosphorylated ATM forms nuclear foci, whereas following alterations in the chromatin structure without detectble DSBs, a diffused staining across the nucleus is observed (Bakkenist and Kastan, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Activated PIKKs phosphorylate various downstream targets involved in controlling cell cycle checkpoints, DNA repair and apoptotic pathways. These include p53, Chk1, Chk2, Brca-1, Rad9, Rad17, H2AX and others (Canman et al, 1998;Cortez et al, 1999;Bao et al, 2001;Chen et al, 2001;Bartek and Lukas, 2003;Stiff et al, 2004). Of particular importance to checkpoint activation is p53 phosphorylation on serine 15.…”
Section: Introductionmentioning
confidence: 99%
“…Of particular importance to checkpoint activation is p53 phosphorylation on serine 15. ATM can directly phosphorylate p53 (Ser15) in response to IR while ATR is critical in the same response to UV (Canman et al, 1998;Tibbetts et al, 1999). Additionally, p53 is phosphorylated on Ser20 by Chk1 or Chk2, which are targets for ATR and ATM signaling, respectively, although some cross-talk exists between the pathways (Bartek and Lukas, 2003).…”
Section: Introductionmentioning
confidence: 99%